2019
DOI: 10.1007/s10295-019-02223-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the microbiota in long- and short-term natural indigo fermentation

Abstract: The duration for which the indigo-reducing state is maintained in indigo natural fermentation batch dependent. The microbiota was analyzed in two batches of sukumo fermentation fluids that lasted for different durations (Batch 1: less than 2 months; Batch 2: nearly 1 year) to understand the mechanisms underlying the sustainability and deterioration of this natural fermentation process. The transformation of the microbiota suggested that the deterioration of the fermentation fluid is associated with the relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Another study showed that a substantial change occurs in the microbiota during the early stage of fermentation, which is characterized by the appearance of Bacillaceae and subsequently by Anaerobranca sp. (93.1% similarity to Anaerobranca gottschalkii and this species belongs to Proteinivoraceae; Tu et al, 2019b). A previous research has shown that an initial drop in ORP is not directly linked to indigo reduction (Aino et al, 2010).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Another study showed that a substantial change occurs in the microbiota during the early stage of fermentation, which is characterized by the appearance of Bacillaceae and subsequently by Anaerobranca sp. (93.1% similarity to Anaerobranca gottschalkii and this species belongs to Proteinivoraceae; Tu et al, 2019b). A previous research has shown that an initial drop in ORP is not directly linked to indigo reduction (Aino et al, 2010).…”
Section: Discussionmentioning
confidence: 85%
“…It was reported that the selection of microorganisms for the initial treatment with hot wood ash extract is important for the selection of necessary microorganisms, which consume oxygen in the early fermentation period (Tu et al, 2019a). In addition, entering stable alkaline anaerobic conditions dominated by obligately anaerobic Anaerobranca is important for the maintenance of an indigo reduced state of fermentation for a long duration (Tu et al, 2019b). Thus, the microbiota in the original material, sukumo, suffered twice from successive environmental pressures (hot wood ash extract and the disappearance of oxygen) at the beginning of the fermentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anode showed stability for 48 h and has possibility to show stability for longer time. The microbiota in the indigo fermentation change slightly in the long term; however, their indigo-reducing activity is maintained for 6-8 months [29,30]. This implies that the MBFC using the indigo-dye fermenting suspension maintains its activity for longer periods.…”
Section: Stability For the Indigo-dye Fermenting Suspension Biofuel Cellmentioning
confidence: 99%
“…Furthermore, such alkaline conditions are convenient for suppressing the growth of contaminated microorganisms. The indigo-dye fermenting suspension can maintain its indigo-reducing activity for long periods even if the microbiota change [29,30]. Consequently, it is unnecessary to maintain sterile conditions.…”
Section: Introductionmentioning
confidence: 99%